Technology surveillance in veterinary vaccine adjuvants (2015-2022): University-industry interaction - Aníbal Domínguez-Odio; Oliver Pérez; Alexander Batista-Duharte; Daniel Leonardo Cala-Delgado (GarVal Editorial Ltda., 2022)
Context: The new generation of immunoenhancers will have to offer solutions to each clinical and technological limitation that currently exists. This innovative context requires periodic technological surveillance by the veterinary biopharmaceutical industry to anticipate technological changes and predict future competitive advantages. Aims: To evaluate the current status, scientific trends, and technological projections in the use of veterinary immunological adjuvants for productive and companion species in the period 2015 and 2021. Methods: The bibliometric analysis included scientific articles on adjuvants in veterinary medicine published in English in 2015-2021 and indexed on the Scopus and Web of Science platforms. All relevant records retrieved between 2015 and 2022 were grouped using the EndNote bibliographic manager, while the analysis of the relational metric indicator was performed and viewed by VOSviewer®. Instead, data on the main commercial veterinary vaccine adjuvants in 2022 were collected from the official websites of 20 veterinary vaccine manufacturers with experience in the market. Results: The academy dedicated 68.2% of its production to disseminating articles with original experimental results with 73.6% being novel notifications about adjuvants of natural, microbial and nanotechnological origin. Industrial production mainly used monoadjuvation (86.9%), inorganic salts adjuvants (48.1%), particularly aluminum hydroxide (43.0%), and classical technology (89.2%) to produce their commercial formulations. Ruminants, swines, and poultry dominated both sectors, with ruminants being the main protagonist. Conclusions: The new scientific knowledge will not have a significant impact on the veterinary pharmaceutical industry in the short term and the hegemonic continuity of traditional adjuvants, in particular aluminum hydroxide, is expected.